The epidemiology and clinical manifestations of mucormycosis: a systematic review and meta-analysis of case reports. (January 2019) - Jeong, W.; Keighley, C.; Wolfe, R.; Lee, W.L.; Slavin, M.A.; Kong, D.C.M.; Chen, S.C.-A.
Abstract: Background: The epidemiology of mucormycosis in the era of modern diagnostics is relatively under-explored. Objectives: To examine the contemporary epidemiology, clinical manifestations, diagnosis and causative pathogens of mucormycosis. Data sources: Ovid MEDLINE and Ovid EMBASE from January 2000 to January 2017. Study eligibility criteria: Published case reports/series of proven/probable mucormycosis. Participants: Patients ≥18 years old. Methods: Patient characteristics, disease manifestations and causative pathogens were summarized descriptively. Categorical variables were assessed by chi-square test or Fischer's exact test, and continuous variables by the Wilcoxon–Mann–Whitney or Kruskal–Wallis test. Risk factors for the different clinical manifestations of mucormycosis were identified using multivariate logistic regression. Results: Initial database searches identified 3619 articles of which 600 (851 individual patient cases) were included in the final analysis. Diabetes mellitus was the commonest underlying condition (340/851, 40%) and was an independent risk for rhino-orbital-cerebral mucormycosis (odds ratio (OR) 2.49; 95% CI 1.77–3.54; p < 0.001). Underlying haematological malignancy was associated with disseminated infection (OR 3.86; 95% CI 1.78–8.37; p 0.001), whereas previous solid organ transplantation was associated with pulmonary (OR 3.19; 95% CI 1.50–6.82; p 0.003), gastrointestinal (OR 4.47; 95% CI 1.69–11.80; p 0.003), or disseminated (OR 4.20; 95% CI 1.68–10.46; p 0.002) mucormycosis. Eight genera (24 species) of Mucorales organisms were identified in 447/851 (53%) cases, of which Rhizopus spp. (213/447, 48%) was the most common. Compared with other genera, Rhizopus spp. was predominantly observed in patients with rhino-orbital-cerebral mucormycosis (75/213, 35% versus 34/234, 15%; p < 0.001). Death was reported in 389/851 (46%) patients. Mortality associated with Cunninghamella infections was significantly higher than those caused by other Mucorales (23/30, 71% versus 185/417, 44%; p < 0.001). However, Cunninghamella spp. were isolated primarily in patients with pulmonary (17/30, 57%) or disseminated disease (10/30, 33%). Conclusions: Findings from the current review have helped ascertain the association between various manifestations of mucormycosis, their respective predisposing factors and causative organisms.